If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x-7)=(19x-13)
We move all terms to the left:
(6x-7)-((19x-13))=0
We get rid of parentheses
6x-((19x-13))-7=0
We calculate terms in parentheses: -((19x-13)), so:We get rid of parentheses
(19x-13)
We get rid of parentheses
19x-13
Back to the equation:
-(19x-13)
6x-19x+13-7=0
We add all the numbers together, and all the variables
-13x+6=0
We move all terms containing x to the left, all other terms to the right
-13x=-6
x=-6/-13
x=6/13
| 36+a=5a | | 1039x=3 | | 7+3x=x | | 2=b-92/2 | | 0.5(8x+2)=7 | | 5.04n-6=85.74 | | 0.05*x=-5 | | –8v+4v=–4v | | 1-2h=-2-7-4h | | 9.5w-2.74=8.7w-7.78 | | 7.49=0.75x+1.39 | | 9q+3=10q | | -2.71+5.7t-8.42=9.8t+8.96 | | -.5w-3/5=1/5w | | (7+2a)=⋅3-20 | | -1(-4z-5)-2=2(2z+5)-6 | | 38.95-11.98=p | | 40=2x(x-4)(x-1) | | M4+m8=12 | | 9p+10=-9+10p+9 | | -6p+5=-7-9p | | X²+12x-32=0 | | x-45=120 | | -8-7h=-8h+2 | | -8b+86=2b-4 | | 91+150+105+3x+2x+x=720 | | 8y+10=-10+5y-10 | | -8b+86=2b-5 | | −21/2b=61/4 | | -125=-5(-4p+5) | | 60y=60y | | x-45=130 |